2019
DOI: 10.3390/ijms20112624
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Homing of Mesenchymal Stem Cells Overexpressing Fibroblast Growth Factor 21 to Injury Site in a Mouse Model of Traumatic Brain Injury

Abstract: Mesenchymal stem cells (MSCs) are emerging as a potential therapeutic intervention for brain injury due to their neuroprotective effects and safe profile. However, the homing ability of MSCs to injury sites still needs to be improved. Fibroblast Growth Factor 21 (FGF21) was recently reported to enhance cells migration in different cells type. In this study, we investigated whether MSCs that overexpressing FGF21 (MSC-FGF21) could exhibit enhanced homing efficacy in brain injury. We used novel Molday IONEverGree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Therefore, it is highly recommended that differentiation assays be performed prior to stem cell delivery to evaluate the influence of SPIO on the differentiation potency of stem cells. In a previous study, it was demonstrated that MSC labeling with the same SPIO type and concentration used in the here did not affect the osteogenic or adipogenic differentiation potency of MSCs 6 .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Therefore, it is highly recommended that differentiation assays be performed prior to stem cell delivery to evaluate the influence of SPIO on the differentiation potency of stem cells. In a previous study, it was demonstrated that MSC labeling with the same SPIO type and concentration used in the here did not affect the osteogenic or adipogenic differentiation potency of MSCs 6 .…”
Section: Discussionmentioning
confidence: 74%
“…This protocol is relevant for MSC labeling and MRI imaging. The procedure for MSC labeling 6 has been previously optimized, and only the steps to prepare labeled MSCs to track in vivo are included here, since in vivo tracking is the focus. The protocol for culturing and labeling of other cell types should be optimized by the researcher.…”
Section: Labeling Of Mscs With Spio Nanoparticlesmentioning
confidence: 99%
“…The potential therapeutic mechanisms comprise replacement of damaged neural cells, promotion of endogenous neural cells, secretion of neurotrophic factors, induction of vascularization and angiogenesis, reduction of apoptosis, and prevention of inflammatory effect 13 . However, the majority of MSC sources for TBI are derived from autologous or allogenic tissues which, therefore, cannot answer how reliable the immune privilege of the MSCs is 14,15 . Additionally, genetic manipulation of the MSC prior to implantation has frequently used in reported studies thus raising another serious issue of tumorigenesis formation 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, cells are mobilized into the peripheral bloodstream and migrate to the damaged tissue or organ [84,85]. Bone marrow-derived MSCs are known to be well capable of homing to numerous injured sites in the body such as myocardial infarction [86,87], traumatic brain injury [88], nephropathy [89], lung injury [90], bone fractures [91] and degenerated IVDs [92,93]. However, knowledge about the exact process and mechanism of how MSCs are mobilized and guided to the effector location is still incomplete.…”
Section: Msc Homing Into An Ivdmentioning
confidence: 99%